Exploring the Mystery of Angiotensin-Converting Enzyme II (ACE2) in the Battle against SARS-CoV-2 - Sharma, Divakar; Sharma, Juhi; Singh, Amit (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
COVID-19 is the newly born pandemic caused by the SARS-CoV-2 virus, which is the recently emerged betacoronavirus that crosses the species barrier. It predominantly infects pneumocytes of the respiratory tract, but due to the presence of angiotensin-converting enzyme II (ACE2) on other cells like surface enterocytes of the upper esophagus and colon, these are also considered as the primary sites of infection. ACE2 receptor served as a cellular entry point for SARS-CoV-2. The expression of the ACE2 receptors is regulated by several factors such as age, tobacco smoking, inflammatory signaling, ACE inhibitors, angiotensin receptor blockers, and comorbidities (chronic obstructive pulmonary disease (COPD), tuberculosis, cerebrovascular disease, coronary heart disease, hypertension, and diabetes). Therefore, scientists are trying to explore the in-depth knowledge of ACE2 and considered it as a potential indirect target for COVID-19 therapeutics. In this focused review, we discussed in detail ACE2 expressions and regulation by different factors in the primary or vulnerable sites of SARS-CoV-2 infections. Clinical trials of rhACE2 in COVID-19 patients are ongoing, and if the outcome of the trials proves positive, it will be a breakthrough for the management of COVID-19. Finally, we suggest that targeting the ACE2 (a master regulator) in a balanced way could serve as a potential option against the management of COVID-19.